Role of metallothionein-like cadmium-binding protein (MTLCdBP) in the protective mechanism against cadmium toxicity in the testis - OHTA, Hisayoshi (Ind Health, 2018)
The role of metallothionein (MT)-like cadmium (Cd) binding protein (MTLCdBP) in protecting the testes against Cd toxicity was examined. In the acute Cd exposure treatment, cadmium chloride was intraperitoneally injected at 2 mg Cd/kg to Wistar male rats. In the chronic Cd toxicity treatments, 20 mg Cd/kg/d was orally administered for 5 d a week for 5, 10, and 15 wk. MT (-I,-II) and MTLCdBP were measured using ELISA and Cd-Hem methods, respectively. Testicular tissues were immunostained with antibodies of MT-I,-II, MT-III, and MTLCdBP. Expression of HO1, OGG, iNOS, COX2, and p53 was measured by RT-PCR. Cd concentration in the testis increased dose-dependently in response to Cd exposure. MTLCdBP concentration increased markedly with increasing Cd accumulation. Significant increases in expression of iNOS, HO1, COX2, and OGG1 were observed in the acute exposure treatment. In the chronic oral administration group, expression of MT-I, MT-II, MT-III, iNOS, HO1, and COX2 did not change. Positive immunostaining of MTLCdBP was observed in testicular interstitial tissue. In the testis protected from Cd toxicity, MTLCdBP induction increased significantly with increasing Cd accumulation. Our results suggest that MTLCdBP plays an important role in protecting the testis against Cd toxicity.